1997
DOI: 10.1016/s0014-5793(97)01103-4
|View full text |Cite
|
Sign up to set email alerts
|

Leptin interacts with glucagon‐like peptide‐1 neurons to reduce food intake and body weight in rodents

Abstract: The adipose tissue hormone, leptin, and the neuropeptide glucagon-like peptide-1 (7-36) amide (GLP-1) both reduce food intake and body weight in rodents. Using dual in situ hybridization, long isoform leptin receptor (OB-Rb) was localized to GLP-1 neurons originating in the nucleus of the solitary tract. ICV injection of the specific GLP-1 receptor antagonist, exendin(9-39), at the onset of dark phase, did not affect feeding in saline pre-treated controls, but blocked the reduction in food intake and body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 26 publications
3
62
1
7
Order By: Relevance
“…In animals con¯icting results on leptin interactions with GLP-1 have been obtained. 42,43 In humans, however, there is no evidence of interactions between GLP-1 and leptin, cholecystokinin or somatostatin. 10,44 ± 46 On the other hand, the inhibition of gastric secretion by GLP-1 has been shown to depend on an intact n. vagus.…”
Section: Glp-1 Appetite and Metabolism In Obesity A Flint Et Almentioning
confidence: 99%
“…In animals con¯icting results on leptin interactions with GLP-1 have been obtained. 42,43 In humans, however, there is no evidence of interactions between GLP-1 and leptin, cholecystokinin or somatostatin. 10,44 ± 46 On the other hand, the inhibition of gastric secretion by GLP-1 has been shown to depend on an intact n. vagus.…”
Section: Glp-1 Appetite and Metabolism In Obesity A Flint Et Almentioning
confidence: 99%
“…In addition, they found that leptin inhibition of food intake can be prevented by blockade of GLP-1 receptor activity. 46 However, this effect does not necessarily suggest GLP-1 receptor involvement in all down-stream actions of leptin. GLP-1 receptor deficient mice have normal body weights, 10 while it is well known that leptin receptor-deficient rodents (db/db mice, fa/fa Zucker rats) become morbidly obese.…”
Section: Glp-1 Reduces Short-term Food Intakementioning
confidence: 97%
“…A administração intra-cerebroventricular de CART e de seu anticorpo específico teve, respectivamente, efeito inibitório e efeito estimulatório da ingestão, sendo sugerido que o peptídeo CART endógeno manteria um tônus inibitório sobre a ingestão alimentar (188). Além disso, a injeção central de CART antes de NPY bloqueia a hiperfagia induzida pelo NPY em ratos normais (188).…”
Section: Transcrito Regulado Por Cocaína E Anfetamina (Cart)unclassified
“…Além disso, a injeção central de CART antes de NPY bloqueia a hiperfagia induzida pelo NPY em ratos normais (188). Ratos submetidos à privação de alimento apresentam redução da expressão de CART no ARC e em modelos animais de obesidade com ausência de sinalização da leptina (camundongo ob/ob, rato Zucker fa/fa) essa expressão é quase nula, sendo estimulada pela administração periférica de leptina (188). Postulou-se que a supressão da ingestão alimentar mediada pela leptina envolveria a diminuição do NPY e a indução do CART (188).…”
Section: Transcrito Regulado Por Cocaína E Anfetamina (Cart)unclassified
See 1 more Smart Citation